2014
DOI: 10.1093/jxb/eru139
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for A-type cyclin-dependent kinase and cyclins for the terminal division in the stomatal lineage of Arabidopsis

Abstract: SummaryCDKA;1 is required for the termial divison of stomatal development. The results presented here use targeted expression to fine-tune the roles of CDKs and cyclins in regulating guard cell production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 43 publications
0
48
0
Order By: Relevance
“…To determine whether other cell parameters were also affected by the enhancer mutation during cotyledon growth, we analyzed cell images collected from 3-to 6-d-old cotyledons (SI Appendix, Fig. S1A) using a different cell-clearing method (30). We found that CA1-1 cells at day 6 also had a slightly smaller area on average than WT and that cae2-1 CA1-1 had the smallest cells at all stages (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether other cell parameters were also affected by the enhancer mutation during cotyledon growth, we analyzed cell images collected from 3-to 6-d-old cotyledons (SI Appendix, Fig. S1A) using a different cell-clearing method (30). We found that CA1-1 cells at day 6 also had a slightly smaller area on average than WT and that cae2-1 CA1-1 had the smallest cells at all stages (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Images of cotyledon cells were collected using either agarose gel imprinting (60) or an ethanol/acetic acid treatment-based method (30). The Shape Factor was determined using the equation (4π × area/perimeter 2 ) as described (29).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the expression of SPCH is under tight and dynamic control, which is crucial for defining stomatal pattern and density. SPCH has been shown to be regulated through phosphorylation by MITOGEN ACTIVATED PROTEIN KINASE (MAPKs), GLYCOGEN SYNTHASE 3 KINASE (GSK3) and CYCLIN DEPENDENT KINASE (CDK) families at the post-translational level (Gudesblat et al, 2012;Lampard et al, 2009;Yang et al, 2014). Phosphorylation by MAPKs or GSK3 targets SPCH for degradation, leading to decreased entry divisions and ultimately a lower stomatal density (Lampard et al, 2009;Gudesblat et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, CYCD4 is involved in stomatal-lineage divisions in the hypocotyls (Kono et al, 2007). Dominant-negative form of CDKB1;1 and CDKA1;1, as well as higher-order mutants of CYCAs inhibit the SCD of GMCs (Boudolf et al, 2004; Yang et al, 2014). It was reported that FLP directly represses CDKB1;1 and CDKA1;1 (Xie et al, 2010; Yang et al, 2014), and FAMA binds to the promoter region of CDKB1;1 (Hachez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%